2016
DOI: 10.1039/c5cc06838j
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using BODIPY–porphyrin dyads for developing deep-red lighting sources

Abstract: Neutral free-base and metallo-porphyrins have been successfully used in organic light-emitting diodes (OLEDs) and solar cells. [1][2][3][4][5] This field is mainly driven by their ease of modification to enhance light-harvesting and photoluminescence (PL) properties based on an efficient energy and/or electron transfer process from moieties attached at the periphery to the porphyrin core.This feature of dyad-like porphyrins is of utmost relevance for lighting schemes, since it could open a new avenue to decoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…It should, however, be acknowledged that a vast majority of the subsequent research on iTMC-LECs have employed an additional electrolyte (often an ionic liquid) in order to attain a reasonably fast turn-on time [4,5]. The LEC field has up until now been dominated by these two principal classes of compounds, although new groups of functional materials, in the form of non-ionic luminescent small molecules [6][7][8][9][10][11][12][13][14], ionic fluorescent small molecules [15][16][17], quantum dots [18,19], and perovskites [20,21], have emerged more recently. Figure 1c presents the chemical structures of a CP, an iTMC, and a luminescent small molecule, as well as a number of electrolytes that have been utilized in recent high-performance LEC devices.…”
Section: Introductionmentioning
confidence: 98%
“…It should, however, be acknowledged that a vast majority of the subsequent research on iTMC-LECs have employed an additional electrolyte (often an ionic liquid) in order to attain a reasonably fast turn-on time [4,5]. The LEC field has up until now been dominated by these two principal classes of compounds, although new groups of functional materials, in the form of non-ionic luminescent small molecules [6][7][8][9][10][11][12][13][14], ionic fluorescent small molecules [15][16][17], quantum dots [18,19], and perovskites [20,21], have emerged more recently. Figure 1c presents the chemical structures of a CP, an iTMC, and a luminescent small molecule, as well as a number of electrolytes that have been utilized in recent high-performance LEC devices.…”
Section: Introductionmentioning
confidence: 98%
“…Compound 1 is bright, green fluorescent dye with similar excitation and emission to fluorescein with several uses in biochemistry, for staining lipids, membranes and other lipophilic compounds, because they exhibit narrow emission bandwidths, they have high extinction coefficient and fluorescence quantum yields and they are photostable. [1] Other applications of these dyes are related to fluorescent probes, [2][3][4] deep-red lighting sources, [5] bioactive CO-releasing molecules [6] and solar cells, [7] amongst many others. [8][9][10] Concerning BODIPY NMR properties, there are several compounds with reported data (Scheme 1) especially related to [11] ; 4, 1 J 11B19F = 33.4 Hz [12] ; 5, 11 B = 0.28, 1 J 11B19F = 28.7 Hz [13] ; 6, 11 B = 0.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, we have demonstrated that an efficient energy transfer process from peripheral BODIPY units to the zinc porphyrin core in dyad-like compounds can be exploited to decouple charge transport and emission processes in LECs. 11 This leads to very stable deep-red emitting devices, but with a moderate efficiency. The latter might be limited by the spin statistics that indicate the formation of excitons with a 1 : 3 spin distribution of singlets and triplets upon electron-hole recombination.…”
mentioning
confidence: 99%
“…Metallated porphyrins have been successfully applied to develop deep-red lighting sources based on the organic lightemitting diode (OLED) [1][2][3][4][5][6][7][8][9][10] and the light-emitting electrochemical cell (LEC) 11 concepts. One of the most important advantages of porphyrins is the mature control of their photophysical features by means of a proper molecular design, namely (i) the expansion of the π-conjugation of the pyrrole unit to red-shift the emission to the near-infra red region, 3 (ii) the use of substituents at the meso position in order to enhance the photoluminescence quantum yields (ϕ), 4 to promote self-assembling, 8,10 and/or to open up the preparation of porphyrin dyads with efficient energy/electron transfer processes, 2,6,9,[11][12][13][14] and (iii) the use of different metal cores to provide new photoluminescence (PL) mechanisms like phosphorescence 2,5,6,8 and thermally activated delayed fluorescence (TADF).…”
mentioning
confidence: 99%
See 1 more Smart Citation